PENGARUH DAYA TARIK WISATA DAN AKSESIBILITAS TERHADAP KEPUTUSAN BERKUNJUNG DENGAN ELECTRONIC WORD OF MOUTH - La Teko; Muhamad Stiadi; Agus Zul Bay (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2026)
This study focuses on determining the "Effect of Tourist Attractions and Accessibility on Visiting Decisions and the role of Electronic Word of Mouth (eWOM) as a mediating variable on Mutiara Beach tourism in Central Buton Regency". Data were collected through observation, documentation, and questionnaire distribution. All tourists who have visited Mutiara Beach in Central Buton Regency became the research population. The Purposive Sampling method was used for sample selection, and the total sample included 140 respondents. SPSS 25 was a tool for testing validity and reliability. The Smart PLS 4.0 application was used to analyze the data using a thin-square-based structural equation model (SEM). This study found that the attractiveness of tourist attractions had a positive and significant impact on visiting decisions. However, accessibility did not significantly or positively influence visiting decisions. EWOM was found to positively and significantly influence visiting decisions; tourist attractions also positively and significantly influenced EWOM; and accessibility also positively and significantly influenced EWOM. EWOM was proven to mediate the relationship between tourist attractions and visiting decisions, as well as accessibility on visiting decisions.